Devastation and renewal : an environmental history of Pittsburgh and its region - Tarr, Joel A. (Joel Arthur), 1934- (History of the urban environment, 2003)
"Today, the steel industry that defined Pittsburgh for over a century is virtually gone. The sky is blue, fish swim in the rivers, and the hillsides are green and lush. The people enjoy access to many large public parks and trails." "In Devastation and Renewal, environmental scholars examine Pittsburgh's process of reclamation, as well as how power was used to cause change or prevent it, and who benefited from environmental initiatives and why. The authors assert that there is still a long road ahead for reclamation and conservation. If a lesson may be taken from history, it is that changes will come along circuitous routes as they have before, often springing from self-interest, and obstructed by battles among competing, civic groups, regional and national government agencies, individuals, and corporations."--Jacket